2016
DOI: 10.1016/j.carbon.2016.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Control of product nature and morphology by adjusting the hydrogen content in a continuous chemical vapor deposition process for carbon nanotube synthesis

Abstract: Floating catalyst chemical vapor deposition (FCCVD) is commonly considered as one of the most attractive process for the production of carbon nanotubes (CNTs). Understanding the phenomena occurring during the FCCVD synthesis of CNTs is critical to improve the process selectivity and scalability. The present work correlates information on gas chemistry and structural characteristics of the carbonaceous products, and show how both are strongly related to the hydrogen content in the reactor. Hydrogen plays differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 53 publications
(65 reference statements)
0
26
2
Order By: Relevance
“…S2 in the ESM), which also occurs in our ethanol system [10,17]. Ma et al [27] suggested that an excess of hydrogen induced fast decomposition of the hydrocarbons (ortho-xylene and acetylene were chosen as a hybrid carbon source), resulting in the accumulation of carbon byproducts on the catalyst surface and slowing down the nanotube growth process. The suppression of the deposition of amorphous carbon at high H2 flow rates could also reduce the yield [29].…”
Section: Effects Of H 2 and N 2 On Swcnt Yield And Diametermentioning
confidence: 72%
See 1 more Smart Citation
“…S2 in the ESM), which also occurs in our ethanol system [10,17]. Ma et al [27] suggested that an excess of hydrogen induced fast decomposition of the hydrocarbons (ortho-xylene and acetylene were chosen as a hybrid carbon source), resulting in the accumulation of carbon byproducts on the catalyst surface and slowing down the nanotube growth process. The suppression of the deposition of amorphous carbon at high H2 flow rates could also reduce the yield [29].…”
Section: Effects Of H 2 and N 2 On Swcnt Yield And Diametermentioning
confidence: 72%
“…S1(d)-S1(f) in the Electronic Supplementary Material (ESM), the quality of the SWCNTs first deteriorates then improves with an increasing of H2 flow rate. This phenomenon can be explained by the formation of amorphous carbon via enhanced decomposition of toluene at a medium H2 concentration and by the gasification of amorphous carbon by hydrogen etching at a high H2 concentration [27,28]. Notably, the yield of carbon deposit decreases with increasing H2 flow ( Fig.…”
Section: Effects Of H 2 and N 2 On Swcnt Yield And Diametermentioning
confidence: 93%
“…Several industrial production techniques employ gas-phase floating catalyst chemical vapor deposition (FCCVD), which allows nanorods and nanotubes to be produced in continuous flow reactors where materials are ultimately collected from the surrounding gas. [8,9,17,[22][23][24] During the production of nanorods and nanotubes within gas-phase reactors, the materials collide due to Brownian motion, resulting in assembly of bundles and in specialized cases, the bundles assemble to form networks of larger-scale structures. When the length scales of the aggregated bundle structures approach the reactor dimensions, gas-phase gelation or aerogelation [25,26] can occur, whereby a macrostructure is formed from the nanomaterial components.…”
Section: Introductionmentioning
confidence: 99%
“…Gas‐phase production is responsible for >90% of commercially produced nanomaterials, including nearly all carbon black and titanium dioxide each with estimated production of 5000–10 000 tonnes annually . Similarly, many 1D materials are commonly synthesized by gas‐phase methods, such as plasma, laser ablation, flame, and hot‐wall reactors. Several industrial production techniques employ gas‐phase floating catalyst chemical vapor deposition (FCCVD), which allows nanorods and nanotubes to be produced in continuous flow reactors where materials are ultimately collected from the surrounding gas …”
Section: Introductionmentioning
confidence: 99%
“…initial growth rate and the characteristic catalyst lifetime 10 . Since then only a few papers were published which attempted to find correlation between gas feed (mostly acetylene as carbon source, argon as carrier and hydrogen as reducing agent) and the characteristics of vertically aligned carbon nanotubes 11 14 .…”
Section: Introductionmentioning
confidence: 99%